FACTORS AFFECTING CABBAGE PRODUCTION IN MAGELANG REGENCY, INDONESIA - Widia Novita Sijabat; Edy Prasetyo; Komalawati (RADJA PUBLIKA, 2026)
Cabbage is a strategic horticultural commodity in Indonesia with high economic value and strong development potential. However, fluctuations in cabbage productivity are often associated with suboptimal allocation of production inputs. This study aims to examine the key factors influencing cabbage production in Magelang Regency, Indonesia. The research was conducted in three districts, Dukun, Pakis, and Ngablak, using a multistage cluster sampling method involving 120 farmers. Data were analyzed using a Cobb-Douglas production function estimated through multiple linear regression. The results indicate that land area, manure, and pesticide use significantly affect cabbage production. These findings highlight the importance of optimizing input allocation and improving farmers’ management practices to enhance agricultural productivity.